Bexmarilimab Activates Human Tumor-Associated Macrophages to Support Adaptive Immune Responses in Interferon-Poor Immune Microenvironments - Rannikko, Jenna H. (AMER ASSOC CANCER RESEARCH, 2025)
Interferons are essential components of the immune response against tumors. The authors identify a possible approach to induce interferons in the tumor microenvironment and promote the effectiveness of other immune therapies relying on preexisting interferon signaling.Immune checkpoint inhibitors (ICI) show substantially greater efficacy in inflamed tumors characterized by preexisting T-cell infiltration and IFN signaling than in noninflamed "cold" tumors, which often remain immunotherapy resistant. The cancer immunotherapy bexmarilimab, which inhibits the scavenger receptor Clever-1 to release macrophage immunosuppression and activate adaptive immunity, has shown treatment benefit in subsets of patients with advanced solid malignancies. However, the mechanisms that determine bexmarilimab therapy outcome in individual patients are unknown. Here we characterized bexmarilimab response in ovarian cancer ascites macrophages ex vivo using single-cell RNA sequencing and demonstrated increased IFN signaling and CXCL10 secretion following bexmarilimab treatment. We further showed that bexmarilimab was most efficacious in macrophages with low baseline IFN signaling, as chronic IFN gamma priming abolished bexmarilimab-induced TNF alpha release. These results highlight an approach to target immunologically cold tumors and to increase the likelihood of their subsequent response to ICIs.